Supportive care needs of oral cancer survivors: Prevalence and correlates. (February 2016) - Lee, Morgan S.; Nelson, Ashley M.; Thompson, Lora M.A.; Donovan, Kristine A.
Highlights: Oral cancer survivors' supportive care needs are understudied. This study examined the unmet needs of oral cancer survivors. Survivors reported substantial unmet needs across all domains. Select variables were related to unmet needs in each domain. Survivors reported high rates of interest in several supportive care services. Summary: Objectives: Many cancer survivors experience unmet supportive care needs. The oral cancer survivor population is growing; however, little is known about the unique needs of this group. The present study aimed to determine the supportive care needs of persons with oral cancer who had completed active treatment at least three months previously. Materials and methods: Oral cancer survivors ( N  = 342) completed an online questionnaire that included the validated Survivors Unmet Needs Survey (SUNS). Relationships between SUNS subscales and various demographic, clinical, and psychosocial variables were examined in univariate and multivariate analyses. Survivors also indicated their top unmet needs and interest in supportive care services. Results: Survivors reported substantial unmet needs across all domains, with many of the top unmet needs falling in the emotional domain. Poorer mental and physical health were associated with greater unmet needs across all domains. In each domain, select demographic and clinical variables also were associated with greater unmet needs in univariate and multivariate analyses. Survivors reported high rates of interest in several supportive care services including support groups and various forms of informational support. Conclusion: The present study highlights the significant burden of unmet supportive care needs in oral cancer survivors who have completed treatment and are coping with long-term ramifications of the disease and its treatment, reveals factors related to those needs, outlines these survivors' interest in a range of supportive care services, and suggests future research directions.